Is Media Literacy Still One of the Priorities for Policy Makers? Interview with David Buckingham and Alexander Fedorov - David Buckingham; Alexander Fedorov (Communication Today, 2025)
The interviews focus on the key question whether media literacy is still in the spotlight of contemporary society. The past decades has seen rapid development of professional and academic interest in the field of media literacy. The theoretical and practical issues that have dominated the field for many years have already drawn attention to the importance of this concept for the individual and for the society. In fact, the introduction of media education in schools and other areas of public life is still being confronted with many challenges. Moreover, the wide range of related problems is becoming less in the centre stage of policy making – at the European and non-European level alike. The interviews address questions about the priorities of educational policy, which should not be focused only on the topics that can directly contribute to economic growth and job creation. Particularly today, at the times of global conflicts and societal as well as cultural transformations, it is very important to develop the critical thinking of citizens – of course, in relation to the media and their society-wide actions and agendas.